Partnering with carryouts: implementation of a food environment intervention targeting youth obesity. Issue 1 (27th December 2017) - Perepezko, K; Tingey, L; Sato, P; Rastatter, S; Ruggiero, C; Gittelsohn, J
Abstract: Youth obesity is a major public health problem in the United States, especially among urban-based, minority youth. The B'More Healthy Communities for Kids (BHCK) trial worked at multiple levels of the food environment, including carryouts, to increase access to and demand for healthy, affordable foods. The objective of this article is to describe the development and implementation of BHCK's carryout intervention. Process evaluation was conducted to assess intervention reach (number of interactions with youth and adults either in person or on social media), dose delivered (number of food samples and promotional materials distributed, social media posts and meetings with owners) and fidelity (availability of promoted items). Overall, the carryout intervention showed moderate to optimal reach, moderate to optimal dose delivered and moderate to optimal fidelity. These findings demonstrate a successfully implemented carryout intervention in a low-income urban setting. Lessons learned about new methods for engaging the community and increasing demand for healthy food can be used to inform future studies and programs to improve the food environment.